KUALITAS AUDIT MEMEDIASI KECAKAPAN MANAJERIAL DAN UKURAN PERUSAHAAN TERHADAP MANAJEMEN LABA PADA PERUSAHAAN F&B YANG TERDAFTAR DI BEI - Ogi Wisnu Saputra; Endah Susilowati (BAJ: Behavioral Accounting Journal, 2020)
This study aims to test and prove managerial skills, company size on earnings management and the effect of audit quality mediate managerial skills and company size on earnings management uses quantitative methods. The population in this study are food and beverage companies listed on the Stock Exchange with a sample of 13 companies. The testing method is done with partial least square which is processed by Smart PLS for Windows Version 3.29. The results of the research conducted showed that managerial skills and company size affect audit quality, while managerial skills and company size do not affect earnings management. Audit quality variables mediate managerial skills and company size on earnings management no effect.